Effect of Vitamin E Against Levels Malondyaldehyde (MDA) and Estrogen Hormone Levels Rats (Rattus Norvegicus) Females Who Exposed to Cigarette Smoke. - Widya Sari Intan (Institute of Computer Science (IOCS), 2020)
Indonesia is one of the countries with the greatest prevalence of smokers in the world. Exposure to cigarette smoke can lead to the physiological impact for women that can inhibit estrogen synthesis in the ovaries and increase levels of Malondyaldehyde (MDA). The purpose of this study to analyze the effect of vitamin E against MDA and estrogen rat (Rattus norvegicus) females were exposed to smoke. This research is an experimental design Post-Test Only Control Group. The total sample consisted of 30 rats females were divided into 5 groups: negative control group without treatment, the positive control group were given exposure to cigarette smoke 1 cigarettes / day and 3 treatment groups P1, P2 and P3 with vitamin E doses of multilevel: 100, 200 and 400 mg / kg / day and exposure to tobacco smoke 1 cigarettes / day. Research carried out for 21 days at Animal house and in the Biomedical Laboratory Faculty of Medicine, University of Andalas Padang. MDA and estrogen hormone levels were measured using ELISA method. Test of significance with One Way ANOVA followed by Bonferroni Multiple Comparisons types. The results showed significant differences (p <0.05) MDA levels between the negative control group (0.53 ± 0.04) positive control group (0.67 ± 0.07). In the estrogen levels also differed significantly (p <0.05) between the negative control group (0.27 ± 0.04) with P2 group (0.38 ± 0.07). In conclusion, there is no effect of vitamin E against MDA both in the negative control group and positive control group.